Exposure Effects Beyond the Epithelial Barrier: Transepithelial Induction of Oxidative Stress by Diesel Exhaust Particulates in Lung Fibroblasts in an Organotypic Human Airway Model. (11th June 2020) - Faber, Samantha C; McNabb, Nicole A; Ariel, Pablo; Aungst, Emily R; McCullough, Shaun D
Abstract: In vitro bronchial epithelial monoculture models have been pivotal in defining the adverse effects of inhaled toxicant exposures; however, they are only representative of one cellular compartment and may not accurately reflect the effects of exposures on other cell types. Lung fibroblasts exist immediately beneath the bronchial epithelial barrier and play a central role in lung structure and function, as well as disease development and progression. We tested the hypothesis that in vitro exposure of a human bronchial epithelial cell barrier to the model oxidant diesel exhaust particulates caused transepithelial oxidative stress in the underlying lung fibroblasts using a human bronchial epithelial cell and lung fibroblast coculture model. We observed that diesel exhaust particulates caused transepithelial oxidative stress in underlying lung fibroblasts as indicated by intracellular accumulation of the reactive oxygen species hydrogen peroxide, oxidation of the cellular antioxidant glutathione, activation of NRF2, and induction of oxidative stress-responsive genes. Further, targeted antioxidant treatment of lung fibroblasts partially mitigated the oxidative stress response gene expression in adjacent human bronchial epithelial cells during diesel exhaust particulate exposure. This indicates that exposure-induced oxidative stress in the airway extends beyond the bronchial epithelial barrier and that lung fibroblasts are both a target and a mediator of the adverse effects of inhaled chemical exposures despite being separated from the inhaled material by an epithelial barrier. These findings illustrate the value of coculture models and suggest that transepithelial exposure effects should be considered in inhalation toxicology research and testing.